Determinant Model of Student Entrepreneurial Intention Based on Islamic Values and Islamic Business Potential Awareness - Silviana Pebruary; Edi Susilo; Musyafa; Kertati Sumekar; Nafi Inayati Zahro; Zuliyanti; Iwan Suroso (JESI (Jurnal Ekonomi Syariah Indonesia), 2026)
Purpose: In the era of increasingly competitive globalization, entrepreneurship is not only an alternative career option but also a strategic solution in reducing unemployment among graduates. This study aims to analyze the factors influencing students' sharia entrepreneurial intentions in the Kudus and Jepara Regencies. Methodology: This study used Path analysis and was conducted with PLS. The sample of this study was 200 students in Kudus and Jepara. Result: Analysis at Kudus shows that only supportive environmental variables significantly affect students' entrepreneurial intentions. Meanwhile, in Jepara, cultural values, a supportive environment, and belief in Islamic values significantly affect business potential. Education, beliefs, and business awareness also positively affect students' Islamic entrepreneurial intentions and development. Overall, the variables in the Kudus model explain 51.8% of the variation in Islamic entrepreneurial intentions, whereas the Jepara model explains 61.1%. Conclusion: Results of this study contribute to the development of an Islamic value-based entrepreneurial intention model through awareness of Islamic business potential as a mediating variable. The factors that form awareness of the potential of Islamic entrepreneurship are more dominant in Jepara. Implications: The research can inform educational institutions and governments in developing programs and policies. However, this study has limitations in describing the change in Islamic entrepreneurial intentions. Follow-up research is recommended using a longitudinal design and expanding area coverage. Originality:This study integrates the variable of Islamic business potential awareness as a mediator between factors that affect Islamic entrepreneurial intentions. Enriching the application of planned behavior theory to Islamic entrepreneurship.